2007
DOI: 10.1007/s11255-007-9242-6
|View full text |Cite
|
Sign up to set email alerts
|

Long-term evaluation of single bolus high dose ATG induction therapy for prophylaxis of rejection in live donor kidney transplantation

Abstract: Although routine single bolus ATG induction significantly reduces the incidence of acute rejection, its long-term beneficial effects on graft function and patient and graft survival are not evident.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…However, several trials fell outside of significance boundaries for infection, CMV infection, and BPAR analysis ( Figure S2). Therefore, we conducted a subgroup analysis without those studies, which included two reports in BPAR (25,38), one in infection (37), and three in CMV infection (17,33,37). Of note, THG, in comparison with ATG-F, was not associated with higher incidences of infection (OR: 1.28; 95% CI: 0.52 to 2.99), CMV infection (OR: 1.15; 95% CI: 0.34 to 4.03), or BPAR (OR: 0.54; 95% CI: 0.30 to 1.11).…”
Section: Publication Biasmentioning
confidence: 99%
“…However, several trials fell outside of significance boundaries for infection, CMV infection, and BPAR analysis ( Figure S2). Therefore, we conducted a subgroup analysis without those studies, which included two reports in BPAR (25,38), one in infection (37), and three in CMV infection (17,33,37). Of note, THG, in comparison with ATG-F, was not associated with higher incidences of infection (OR: 1.28; 95% CI: 0.52 to 2.99), CMV infection (OR: 1.15; 95% CI: 0.34 to 4.03), or BPAR (OR: 0.54; 95% CI: 0.30 to 1.11).…”
Section: Publication Biasmentioning
confidence: 99%
“…Furthermore, lower doses may not effectively reduce the rate of allograft rejection (10). The dose of thymoglobulin is determined according to the weight of the patient and is administered at a dose of 1.5 mg to a maximum of 5 mg/g body weight for 3 to 10 days (15)(16)(17). The results of various studies are different on the rate of acute rejection of allograft, survival of patients and the transplanted kidney, and also the side effects of thymoglobulin.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed the efficacy of a bolus ATG dose in reducing acute rejection, with subsequent patient and graft survival being comparable. 27 Alemtuzumab study A pilot study was carried out in 2 phases by using alemtuzumab (30 mg) induction. In phase 1, 21 patients were randomized to receive either tacrolimus (11 patients) or sirolimus (10 patients).…”
Section: Antithymocyte Globulin Trialmentioning
confidence: 99%